A Multifaceted FISH Approach to Study Endogenous RNAs and DNAs in Native Nuclear and Cell Structures. (24th September 2015) - Byron, Meg; Hall, Lisa L.; Lawrence, Jeanne B.
Abstract: Fluorescence in situ hybridization (FISH) is not a singular technique, but a battery of powerful and versatile tools for examining the distribution of endogenous genes and RNAs in precise context with each other and in relation to specific proteins or cell structures. This unit offers the details of highly sensitive and successful protocols that were initially developed largely in our lab and honed over a number of years. Our emphasis is on analysis of nuclear RNAs and DNA to address specific biological questions about nuclear structure, pre‐mRNA metabolism, or the role of noncoding RNAs; however, cytoplasmic RNA detection is also discussed. Multifaceted molecular cytological approaches bring precise resolution and sensitive multicolor detection to illuminate the organization and functional roles of endogenous genes and their RNAs within the native structure of fixed cells. Solutions to several common technical pitfalls are discussed, as are cautions regarding the judicious use of digital imaging and the rigors of analyzing and interpreting complex molecular cytological results. Curr. Protoc. Hum. Genet . 76:4.15.1‐4.15.21. © 2013 by John Wiley & Sons, Inc.